2018
DOI: 10.5578/mb.57534
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Pertussis Toxin Antibody in Manisa Province of Turkey, After Six Years Implementation of Acellular Pertussis Vaccine

Abstract: Vaccination is the most effective way of preventing pertussis disease. Turkey commenced a routine infant immunization program using whole cell (wP) pertussis vaccine in 1968. Immunization accelerated in 1985 after participation of Turkey in the Expanded Programme on Immunization initiated by the World Health Organization. Acellular vaccine (aP) replaced wP in 2008 and a booster was added to age 6 in 2010. The immunization programme was successful in reducing the morbidity rate from 20.58 per 100.000 in 1970 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…27 In another study of patients between 2 and 80 years old, anti-PT IgG antibodies were found to be lowest at 11 years old and highest at 15 years old. 28 The authors suggested that the high levels of anti-PT IgG antibodies detected in 15-year-olds were due to pertussis infection. 28 In another study, Bordetella pertussis positivity was found in 19.8% of children who had a cough for more than two weeks between the ages of 7 and 18.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 In another study of patients between 2 and 80 years old, anti-PT IgG antibodies were found to be lowest at 11 years old and highest at 15 years old. 28 The authors suggested that the high levels of anti-PT IgG antibodies detected in 15-year-olds were due to pertussis infection. 28 In another study, Bordetella pertussis positivity was found in 19.8% of children who had a cough for more than two weeks between the ages of 7 and 18.…”
Section: Discussionmentioning
confidence: 99%
“…28 The authors suggested that the high levels of anti-PT IgG antibodies detected in 15-year-olds were due to pertussis infection. 28 In another study, Bordetella pertussis positivity was found in 19.8% of children who had a cough for more than two weeks between the ages of 7 and 18. 29 The results of the present study indicate that physicians do not have sufficient knowledge of Tdap immunization for adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Özbek et al found that 14% for anti-HAV total and 18% for anti-HBc total were unnecessarily repeated tests between May 2002 and May 2005 at Dokuz Eylül University. [11] Özbek examined unnecessary test requests from hepatitis B vaccinated patients between 2007 to 2009 and found that 24.6% of anti-HBs positive patients had repeat tests and 12.9% of other parameters (HBsAg, anti-HBc, anti-HBc IgM, HBeAg, anti-HBe) were unnecessarily requested. [5] In their study evaluating inappropriate test rerequests for HbsAg, anti-HCV, and antihuman immunodeficiency virus antibody tests performed at Sakarya University Training and Research Hospital between January 2009 and December 2013, Demiray et al found a re-request rate of 20.2% and a financial loss of 6489 US dollars.…”
Section: Discussionmentioning
confidence: 99%
“…[11] Özbek examined unnecessary test requests from hepatitis B vaccinated patients between 2007 to 2009 and found that 24.6% of anti-HBs positive patients had repeat tests and 12.9% of other parameters (HBsAg, anti-HBc, anti-HBc IgM, HBeAg, anti-HBe) were unnecessarily requested. [5] In their study evaluating inappropriate test rerequests for HbsAg, anti-HCV, and antihuman immunodeficiency virus antibody tests performed at Sakarya University Training and Research Hospital between January 2009 and December 2013, Demiray et al found a re-request rate of 20.2% and a financial loss of 6489 US dollars. [12] Genç et al found that the total number of unnecessary HBV serologic tests performed at Dumlupınar University between 2011 to 2013 was 3.01%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation